STRATEGI PEMBELAJARAN MELALUI PEMBERIAN REWARD UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III SDN 01 MENTAWA TAHUN PELAJARAN 2023-2024 - Kurniatika; Oskar Hutagaluh, Bayu (ADISAM PUBLISHER, 2025)
This thesis discusses Learning Strategies Through the Provision of Rewards to Increase the Learning Motivation of Grade III Students of SDN 01 Mentawa for the 2023-2024 Academic Year. This research has two objectives, namely: Implementation of reward strategies to increase student learning motivation. 2) Impact of student learning motivation or rewarding. This study uses a qualitative approach and a type of phenomenological research. Data collection techniques use interviews, observations, and documentation. Data analysis techniques use data collection, data reduction, data presentation, and conclusion drawn. The technique of checking the validity of the data uses source triangulation and membercheck. The results of the study show that: 1. The implementation carried out by grade III teachers in giving rewards is the first by preparing the lesson plan before teaching, the second is by looking at the situation and condition of the students in the classroom, whether they are ready to learn, the third provides an explanation of the material, the fourth gives questions to students when explaining, and the last one gives rewards both verbal and non-verbal. 2. The impact of the learning motivation of grade III students of SDN 01 Mentawa on the provision of rewards is showing a positive impact on learning motivation, student participation or activeness in learning and student enthusiasm. The form of reward used, both verbal (praise, applause) and non-verbal (rewards), can increase students' activeness in learning so that students feel enthusiastic and motivated to study diligently